Why mental disorders are brain disorders. And why they are not: ADHD and the challenges of heterogeneity and reification - Schleim, Stephan (Frontiers in Psychiatry, 2022)
Scientific attempts to identify biomarkers to reliably diagnose mental disorders have thus far been unsuccessful. This has inspired the Research Domain Criteria (RDoC) approach which decomposes mental disorders into behavioral, emotional, and cognitive domains. This perspective article argues that the search for biomarkers in psychiatry presupposes that the present mental health categories reflect certain (neuro-) biological features, that is, that these categories are reified as biological states or processes. I present two arguments to show that this assumption is very unlikely: First, the heterogeneity (both within and between subjects) of mental disorders is grossly underestimated, which is particularly salient for an example like Attention Deficit/Hyperactivity Disorder (ADHD). Second, even the search for the biological basis of psychologically more basic categories (cognitive and emotional processes) than the symptom descriptions commonly used in mental disorder classifications has thus far been inconclusive. While philosophers have discussed this as the problem of mind-body-reductionism for ages, Turkheimer presented a theoretical framework comparing weak and strong biologism which is more useful for empirical research. This perspective article concludes that mental disorders are brain disorders in the sense of weak, but not strong biologism. This has important implications for psychiatric research: The search for reliable biomarkers for mental disorder categories we know is unlikely to ever be successful. This implies that biology is not the suitable taxonomic basis for psychiatry, but also psychology at large.